Antibacterial mode of action of the hydroethanolic extract of Leonotis nepetifolia (L.) R. Br. involves bacterial membrane perturbations. (22nd August 2015) - Oliveira, Darley Maria; Melo, Fernanda Germano; Balogun, Sikiru Olaitan; Flach, Adriana; de Souza, Edineide Cristina Alexandre; de Souza, Gilmar Prado; Rocha, Iolanda do Nascimento Araújo; da Costa, Luiz Antonio Mendonça Alves; Soares, Ilsamar Mendes; da Silva, Larissa Irene; Ascêncio, Sérgio Donizeti; de Oliveira Martins, Domingos Tabajara
Abstract: Ethnopharmacological relevance: Leonotis nepetifolia (L) R. Br., Lamiaceae, a pantropical shrub, popularly known in Brazil as "cordão-de-frade", "rubim", is reportedly used in Brazilian ethnomedicine as well as in different countries in the treatments of ailments such as infections, inflammations, wounds, stomach disorders, among others. Aim of the study: To evaluate its potential cytotoxicity and antibacterial mode of action of the hydroethanolic extract of L. nepetifolia (HE Ln ) leaves, including phytochemical analysis. Materials and methods: The cytotoxicity of HE Ln was investigated by Alamar blue assay, using CHO–K1 cells. Antibacterial activity of HE Ln was tested by broth microdilution methods against a panel of bacteria of clinical interest. The mode of action of L. nepetifolia was studied by targeting bacterial membranes. Phytochemical analysis was performed by determining total secondary metabolites with spectrophotometric assays and HPLC. Results: HE Ln is not cytotoxic in the in vitro evaluation (IC50 >200 μg/mL). It demonstrated a good spectrum of antibacterial activity with major activity against Shigella flexneri, Enterococcus faecalis, Staphylococcus aureus and Bacillus subtilis with MIC=6.25 µg/mL, Helicobacter pylori with MIC of 25 µg/mL and Streptococcus pyogenes with MIC of 50 µg/mL. Its mode of action is associated, at least partly, with changes in the permeability of bacterial membranes, as evidenced by the increased entry of hydrophobic antibiotics in Shigella flexneri and intense efflux of K + and nucleotide leakage in E. faecalis and Shigella flexneri . In addition, the presence of phenols, flavonoids and carotenoids, described in the literature to possess antibacterial effects, were detected in the composition of HE Ln, with high phenol content (11.55%), especially the flavonoids (6.47%). Conclusion: The results indicate that HE Ln has low cytotoxicity and potent antibacterial activity. It is bacteriostatic in nature, possibly acting at the level of bacterial membranes, especially on the cytoplasmic membrane and outer membrane, thus supporting its popular use in infectious processes. In addition, the presence of phenols, flavonoids, carotenoids, fatty acids and steroids, described in the literature as possessing antimicrobial activity, were detected in the composition of HE Ln . Graphical abstract: